Intraoperative accidents associated with surgical removal of third molars - Aline Monise Sebastiani; Sara Regina Barancelli Todero; Giovana Gabardo; Delson João da Costa; Nelson Luis Barbosa Rebelatto; Rafaela Scariot (Universidade Estadual de Campinas, 2014)
Aim: To evaluate the prevalence of intraoperative accidents associated with extraction of third molars and identify possible risk factors. Methods: Prospective study with patients undergoing third molar surgery by residents of the Oral and Maxillofacial Surgery Service at the Federal University of Parana. Epidemiological data were collected from preoperative evaluation forms. During the surgical procedure were evaluated the radiographic position classifications of all third molars removed, using methods such as osteotomy and/or tooth section, time for the procedure and occurrence of any complication. Results: The students extracted a total of 323 teeth. The mean surgical time was 45 min. Conclusions: The prevalence of intraoperative accidents during extraction of third molars was 6.19%. The most prevalent accident was maxillary tuberosity fracture, followed by hemorrhage. Age, positioning of the teeth and use of the techniques of osteotomy and tooth section are possible risk factors.